Voltage-Controlled Small Signal Analysis of Real Space Transfer Transistor - K. F. Yarn; J. Y. Hwang (Active and Passive Electronic Components)
The research of determining the small signal equivalent circuit of the real space transfer (RST) transistor is investigated in this work. We propose a voltage-controlled mode model, called parameter extraction, to describe the performance of RST transistors at high frequency range. Besides, we also employ the value-determined model to simulate the microwave characteristics of RST and the theoretical and experimental results are compared. The influence of variables of RF performance is analyzed and theoretical results show that the cut-off frequency (fT) is mainly affected by the leakage resistances and the dimension of metal contact, but the maximum available gain frequencyfmax, is dependent on contact resistances.